Academic mobility and the experiences of foreign staff at South African higher education institutions - Sehoole, C.; Adeyemo, K.S.; Ojo, E.; Phatlane, R. (South African Journal of Higher Education, 2019)
This article analyses the patterns of international academic mobility in higher education with particular focus on academic staff. Using the ‘pull and push factors’ as a conceptual framework, it argues that the patterns of international academic staff mobility follow the pattern of international cross-border migrants. These are driven mainly by the pull factors which include quest for better opportunities in life including education. The article uses three sources of data namely documentary analysis, statistical data from the Department of Education’s Higher Education Management Information System (HEMIS), and data from questionnaires that were distributed to international academic staff at the three South African universities; namely, the University of Pretoria, University of South Africa, and University of the Witwatersrand. For the international academic staff working in South Africa, it was demonstrated that they have both positive and negative experiences. The negative experiences seem to be related to the major nation building project to overcome racism and xenophobia. The principles of non-racialism and, non-discrimination need to be promoted in order to build an inclusive and socially coherent society.